Pengaruh Kompensasi Terhadap Turnover Intention Dengan Job Embeddedness Sebagai Variabel Intervening (Studi Pada Karyawan Di PT. Primissima) - Zakaria, Royan; Astuty, Isthofaina (Jurnal Manajemen Bisnis, 2017)
This study aims to analyze the effect of compensation on turnover intention with job embeddedness as intervening variable of study on PT. Primissima employees. Subjects in this study were employees in the production of PT. Primissima. The number of samples used were 109 respondents using cluster sampling and convenience techniques. The analysis technique used for this test is SEM (Structural Equation Modeling) using AMOS software version 22. Based on the analysis, the result shows that compensation has negative and significant effect on turnover intention, compensation has positive and significant effect on job embeddedness, compensation has negative and significant effect on turnover intention, and job embeddedness does not mediate the effect of compensation to turnover intention on PT production employee Primissima.